DESIGN OF LEARNING UNITS FOR SCHOOL PHYSICAL EDUCATION WITH 6TH GRADE STUDENTS (University Arena, 2025)
Background. From the unitary documents of the teacher of physical education, the didactic design acquires a personalized and individual character, regarding the distribution of the learning units in lessons and throughout the school year, the joining of the learning units into lessons, the placement of the test events for the sunmative evaluation and of the tests stipulated by the National School System of Evaluation, as well as those established by the teacher in the structure of the school year.Objectives. This research aimed at the following objectives: to present the theoretical documentation of the didactic design in school physical education, particularly the learning units; to carry out the half-yearly test events evaluation; to make the didactic design of the learning units necessary for the teaching-learning-evaluation of the education contents of the motor qualities and skills specific to basketball game; to apply the evaluation system of the test events; to analyze the effectiveness of the didactic design, the achievement of the learning units in basketball and the motor skills of the 6th grade students; to draw conclusions and develop practical recommendations.Methods. This scientific approach entailed the organization of a study in the Secondary School no. 28 of Bucharest, with a group of 24 students of the 6th C grade; the study was conducted over the 2017-2018 school year, the first semester. The following research methods were used in this paper: study of the specialized literature, method of pedagogical observation, method of the experimental study, method of tests, statistical-mathematical method and graphical representation of results. This study also includes the final results of the specialty inspection for obtaining the teaching certification level II by the first author, highlighting the efficiency of the didactic design of the learning units used during the instructive-educational process of teaching-learning-evaluation of the 6th C grade students. There were also applied 4 test events selected from the National School System of Evaluation for 6th grade students, regarding the speed evaluated by 50 m speed running, explosive power evaluated by standing long jump, endurance evaluated by endurance running (girls – 600 m and boys – 800 m) and sports game – basketball.Results. The study results prove the efficiency of using the actuation techniques for the development of body segments muscles tonicity, the achievement of motor actions with different efforts and structures and progressive degree of complexity specific to basketball and the integration of the learnt technical procedures into simple tactical actions of the basketball game. The application of the test events evaluation system in 6th grade students highlighted the level of development of the running speed, a low level of the explosive power of the lower limbs, endurance running 600 m girls and 800 m boys and the level of learning the motor and technical-tactical actions specific to the basketball game.Conclusion. Performing the didactic design of the learning units in school physical education for the 6th grade students contributed to the achievement of the reference objectives of the education contents of “power” motor skill in basketball and to proposing the recommendations needed to improve the teaching-learning-evaluation process at this level.
Keywords: basketball; strength; evaluation; contents; learning units; test events